2018
DOI: 10.1364/oe.26.028312
|View full text |Cite
|
Sign up to set email alerts
|

Pulse length variation causing spectral distortions in OPO-based hyperspectral coherent Raman scattering microscopy

Abstract: Picosecond optical parametric oscillators (OPOs) with broad wavelength tunability are frequently used as light sources in hyperspectral coherent Raman scattering (CRS) microscopy. We investigate how changes in the pulse length during OPO wavelength tuning of the pump beam affect hyperspectral CRS imaging. We find that significant distortions of the resulting CRS spectra occur if the OPO is operated without monitoring pulse length variations. By utilizing a custom-written MATLAB based control program to counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Another advantage is that the pulse‐width remains constant over the entire tuning range, so there is no need for additional pulse‐width control as in commercial OPO hyperspectral operation. [ 48 ] The low‐intensity fluctuations and the high power spectral density of both the pump and Stokes beams enable HS‐CRS microscopy, particularly SRS microscopy with excellent signal‐to‐noise ratio (SNR). We demonstrated that the SNR of the SRS images is at least similar to those obtained by a commercial OPO.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage is that the pulse‐width remains constant over the entire tuning range, so there is no need for additional pulse‐width control as in commercial OPO hyperspectral operation. [ 48 ] The low‐intensity fluctuations and the high power spectral density of both the pump and Stokes beams enable HS‐CRS microscopy, particularly SRS microscopy with excellent signal‐to‐noise ratio (SNR). We demonstrated that the SNR of the SRS images is at least similar to those obtained by a commercial OPO.…”
Section: Discussionmentioning
confidence: 99%
“…readily built into the popular scan control software ScanImage [19], early open access versions of which are still available and which we e.g. use to operate custom-build coherent Raman scattering microscopes [29]. For the acquisition of a single-raw image, the EOM first shutters the laser beam and the scanning mirrors are moved to the start of the first illuminated line of the overall pattern.…”
Section: Methodsmentioning
confidence: 99%
“…readily built into the popular scan control software ScanImage [ 19 ], early open access versions of which are still available and which we e.g. use to operate custom-build coherent Raman scattering microscopes [ 29 ].…”
Section: Methodsmentioning
confidence: 99%